DEVELOPMENT OF PLASMID DNA MOLECULES FOR IDENTIFICATION, DETECTION, AND INTEGRATION OF GENES (International Journal of Food and Nutritional Sciences, 2022)
In this research, DNA degradation andPCR amplification of transgenic andnontransgenic maize DNA wereinvestigated under thermal treatment at100°C and 121° C for 300 min